Development of an Acid Resistant Concrete: A Review - Khitab, Anwar; Arshad, Muhammad Tausif; Awan, Faisal Mushtaq; Khan, Imran (International Journal of Sustainable Construction Engineering and Technology, 2013)
This review paper addresses the measures taken to prevent or minimize the deterioration of concrete, which confronts an acidic environment. Primarily, the mechanism of reaction between alkaline concrete and acid is clearly demonstrated. The mechanism of reaction clearly sets guidelines as to how the chances of this disastrous reaction should be minimized or eliminated at all. The suggested preventive measures are two-fold i.e. the improvement of the basic microstructure of concrete and the provision of barriers against acids. Concrete can be made acid resistant using classical as well as novel techniques like nanotechnology. There exists an immense need that these measures are recognized and implemented by the construction industry to put a stop to huge money losses.